The colonial linguistics of governance in Sudan: the Rejaf Language Conference, 1928. Issue 3 (1st September 2016) - Abdelhay, Ashraf; Makoni, Busi; Makoni, Sinfree
Abstract : This paper explores the discursive history of 'language-making' in the context of the Anglo-Egyptian Sudan, focusing on a significant colonial moment of standardisation: The Rejaf Language Conference (RLC) of 1928. Through inspecting the report of the proceedings of the RLC, the paper contends that this institutional event contributed to the construction of racial and regional differences by, then: (1) being informed by scientific theories of racial categorisation as an epistemological basis for creating a stratified local sociolinguistic system; (2) with a Eurocentric audience design, inventing 'technical versions' of 'local vernaculars' and 'language groups' imbued with specific indexical values, anchored to specific localities and social identities; (3) relationally, vernacularising Arabic by reworking its ideological load and orthographic order determined by a colonial economy of education; (4) artefactualising a pluralistic image of the society as an effect and function of institutional linguistic classification of forms tied to specific localities and people; and (5) resulting in the planned absence of a perceived 'indigenous' lingua franca in the Southern Sudan. The RLC as a relatively regimented format, characterised by a rationalised absence of the 'local voice', was one of the significant contexts in which the very disciplinary identity of linguistics was rationalised, resisted, and maintained.